Functional optic tract rewiring via subtype- and target-specific axonal regeneration and presynaptic activity enhancement - Xin Zhang; Chao Yang; Chengle Zhang; Junqiang Wu; Xiang Zhang; Jiayang Gao; Xuejie Wang; Leung Ting Chan; Yiren Zhou; Yujun Chen; Sindy Sing Ting Tam; Shuhang Chen; et al. (Nature Communications)
Abstract Mechanisms underlying functional axonal rewiring after adult mammalian central nervous system (CNS) injuries remain unclear partially due to limited models. Here we develop a mouse intracranial pre–olivary pretectal nucleus (OPN) optic tract injury model and demonstrate that Pten/Socs3 knockout and CNTF expression in retinal ganglion cells (RGCs) promotes optic tract regeneration and OPN reinnervation. Revealed by transmission electron microscopy, trans-synaptic labeling, and electrophysiology, functional synapses are formed in OPN mainly by intrinsically photosensitive RGCs, thereby partially restoring the pupillary light reflex (PLR). Moreover, combining with Lipin1 knockdown accelerates the recovery and achieves functional reconnection after chronic injury. PLR can be further boosted by increasing RGC photosensitivity with melanopsin overexpression, and it can also be enhanced by treatment of a voltage-gated calcium channel modulator to augment presynaptic release. These findings highlight the importance of neuronal types and presynaptic activity for functional reconnection after CNS injuries.